Representasi Kepemimpinan dalam Film Sultan Agung Karya Hanung Bramantyo - Noval, Fikriandrian; Agung Putra Mulyana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the representation of Sultan Agung’s leadership in the film Sultan Agung directed by Hanung Bramantyo, using a descriptive qualitative approach. The research highlights how film as a medium constructs the meaning of leadership through narrative, visual elements, cultural symbols, and character development. Stuart Hall’s theory of representation is utilized to understand meaning construction in film, while leadership analysis refers to charismatic, transformational, and authoritarian models. Roland Barthes’ semiotic analysis is applied to examine denotation, connotation, and myth within the film’s elements. Data were collected through observation, documentation, interviews, and literature study, then systematically processed and analyzed. The findings show that Sultan Agung portrays not only a historical figure of leadership but also reflects cultural values and national identity relevant to contemporary Indonesia. The representation of leadership is constructed through cultural symbols, dialogues, and a meaningful storyline, generating new discourse about the ideal leader in modern society. This study is expected to enrich media and leadership studies and contribute to the development of contextual leadership insight among the younger generation.